Effect of Artesunate on Peripheral Parasitaemia in Pregnant Women with Plasmodium Falciparum Infection: Efek Artesunat pada Perempuan Hamil dengan Infeksi Plasmodium Falciparum terhadap Kejadian Parasitemia Perifer - Susi W Saragih; St. Maisuri T. Chalid; Umar Malinta; Isra Wahid (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the effect of artesunate on peripheral parasitaemia in pregnant women with Plasmodium falciparum infection. Methods: Pregnant women in second and third trimester with Plasmodium falciparum infection and their newborns were included in cohort prospective study in Sorong West Papua from September 2015 to February 2016. All pregnant women received 200 mg orally artesunate monotherapy for 7 days. Their newborns examined for weight at delivery and parasitaemia in placenta and cord blood. Parasitaemia diagnosis by Rapid Diagnostic Test and blood smear microscopy. Results: After artesunatemonotherapy, 82.5% (33/40) malariainfected pregnant women had negative parasitaemia (p=0.000) although 17.5% (7/40) of the pregnant women had positive parasitaemia. Parasitaemia also found in 10% (4/40) of placenta and 7.5% (3/40) of umbilical cord from newborns of malaria-infected pregnant women treated with artesunate. 70% (28/40) of the newborns in this study had normal weight. Conclusion: Artesunate reduces peripheral parasitaemia in the second and third trimester of pregnancy, and is associated with normal birth weight. [Indones J Obstet Gynecol 2017; 5-3: 135-138] Keywords: artesunate, low birth weight, peripheral parasitaemia